Zelenka and the Combinative Impulse: Contrapuntal Techniques in the Miserere in D Minor, ZWV 56. Issue 2 (3rd July 2019) - Collins, Denis
Abstract : Commissioned in 1722 for the Holy Week services at the Dresden Hofkapelle, Zelenka's Miserere in D minor (ZWV 56) demonstrates virtuosic handling of a wide range of contrapuntal techniques. Zelenka drew upon his deep knowledge of past musical traditions, honed through his earlier studies in Vienna with Fux and his circle, to provide individual sections of the Miserere with systematic explorations of freely imitative, canonic and fugal writing as well as subtle demonstrations of invertible counterpoint, retrograde motion and melodic inversion. The result is a work that offers insight into Zelenka's abilities to exploit the combinative potential of his motivic materials in settings that maintain expressive as well as technical originality. The present study adopts a range of analytical techniques to uncover the inner workings of Zelenka's counterpoint, thereby providing greater understanding of this composer's versatility and accomplishments.